2013
DOI: 10.5539/mas.v7n12p15
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Web Atmospherics on Entertainment Gratification and Web Irritation: Some Empirical Evidence from Online Shopping

Abstract: The difficulty in converting web browsers into actual online customers remains a problem for many online retailers. While previous studies have suggested that online retailers should strive to increase entertainment gratification and reduce web irritation among online consumers, they lack empirical evidence to support the manipulation of web atmospherics toward this end. The research presented here establishes and tests the conceptual links of web atmospherics, entertainment gratification and web irritation. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…Consumers were more emotionally confused (i.e., annoyed, irritated, and unnerved) when they experienced high messiness in a low crowded environment. These results support the prior literature on messiness, which suggests that messy shopping ambience can negatively affect human anxiety, distract consumers' attentions, and dilute human experiences thus leading to irritation and confusion (Ducoffe, ; Lim, ). Further, prior literature suggests an inverted U‐shaped relationship between visual complexity and customers' approach behaviors (Gilboa & Rafaeli, ; Jang et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…Consumers were more emotionally confused (i.e., annoyed, irritated, and unnerved) when they experienced high messiness in a low crowded environment. These results support the prior literature on messiness, which suggests that messy shopping ambience can negatively affect human anxiety, distract consumers' attentions, and dilute human experiences thus leading to irritation and confusion (Ducoffe, ; Lim, ). Further, prior literature suggests an inverted U‐shaped relationship between visual complexity and customers' approach behaviors (Gilboa & Rafaeli, ; Jang et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…In turn, having trust in e-retailers positively influences their intentions to e-shop. These findings conform to Lim's (2013a) findings that e-shopping experiences that are fruitful, safe, and secure give rise to trust and increase the likelihood of subsequent e-purchases. Given this trait of e-CB, this study recommends that e-retailers consider engaging in follow-up activities to ensure that e-shoppers develop loyalty (i.e.…”
Section: Actual E-shopping Purchase and Post-purchase Evaluationssupporting
confidence: 92%
“…Several studies have suggested that similar forms of atmospherics in offline retailers can be applied to online retailers, called "web atmospherics" (WA), in the context of e-shopping (Eroglu et al, 2003;Dailey, 2004;Lim, 2013a). Although tools to incorporate certain offline atmospheric cues, such as touch and aroma, to the online world are available (e.g.…”
Section: Integration Of Es and Wamentioning
confidence: 99%
“…Cronbach's ␣ was 0.89 for this scale above threshold of 0.7 recommended by Nunnally and Bernstein [86]. Perceived irritation was measured by three items-scale used in previous studies [75,76,79,87]. Sample item was "I feel that most online shopping websites are irritating" (Cronbach's ␣ was 0.93).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, perceived irritation have negative effect on vendor dynamics like competence, integrity and credibility [79]. Even with several studies of negative attributes of perceived irritation on shopping online, there has been little or no research work aimed at investigating indirect effect of perceived irritation of consumers' reviews posted online on different social media platforms.…”
Section: Moderating Role Of Perceived Irritationmentioning
confidence: 99%